Pengaruh Perputaran Kredit dan Perubahan Tingkat Suku Bunga pada Return on Asset Lembaga Perkreditan Desa Denpasar - Manuarsa, I Made Candra Dedi; Affandy, Didied Poernawan (Universitas Batanghari Jambi, 2024)
Lembaga Perkreditan Desa (LPD) serves as a credit lending institution to local villagers in accordance with Bali Province Regional Regulation Number 3 of 2007. As the continuous LPD profitability declines since 2018, the institution strives to boost its profitability in 2021 to improve its credit turnover and change the interest rates. this study aims to determine the effect of credit turnover and interest rate changes on the return on assets of LPD Denpasar, and employs the risk theory of profit as the research theoretical basis involving the saturated samples of 35 LPDs in Denpasar. The results of the panel data analysis utilizing Eviews 12 exhibit that this study conform to the risk theory of profit, revealing the positive correlation of credit turnover on ROA, and interest rates changes which have a negative effect on ROA.